2016
DOI: 10.3311/ppci.8631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Triaxial Behavior of a Sand with Disaccharide

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The pore fluid viscosity changes the properties of minerals and pore fluid contacts, thereby facilitating the displacement of particles relative to each other and displaying reduction in strength. These findings are supported by the results that were reported by Ratnaweera and Meegoda (2006) and Cabalar andClayton (2010 and. Therefore, the main reason for the reduction of strength due to 10 and 15% glycerol is viscosity.…”
Section: Discussionsupporting
confidence: 88%
“…The pore fluid viscosity changes the properties of minerals and pore fluid contacts, thereby facilitating the displacement of particles relative to each other and displaying reduction in strength. These findings are supported by the results that were reported by Ratnaweera and Meegoda (2006) and Cabalar andClayton (2010 and. Therefore, the main reason for the reduction of strength due to 10 and 15% glycerol is viscosity.…”
Section: Discussionsupporting
confidence: 88%
“…Many researchers have studied AGF and its effects on soil properties and mechanical behavior of frozen soils [20][21][22][23][24][25][26][27][28][29]. However, compared with unfrozen soils a greater effort is required to study frozen soils [30][31][32][33]. A mine shaft project near Swansea in South Wales is the first recorded application of AGF in 1862 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high temperature has been reported to reduce the soil strength and enhance crack formation [21]. Cabalar found that higher temperature leads to a jump in pore water pressure [22]. We determined that the strength of the red clay and expansive soil decrease with increasing temperature (from −4 to 60 • C), and red clay, in particular, exhibits higher heat sensitivity [23].…”
Section: Introductionmentioning
confidence: 99%